Marker assisted gene pyramiding of leaf rust resistance genes Lr 9, Lr 24 and Lr 28 in a bread wheat cultivar HD 2329 - Charpe, Ashwini; Koul, Sunita; Gupta, Sudhir Kumar; Singh, Anupam; Pallavi, Jutru Kumari; Prabhu, Kumble Vinod (Journal of Cereal Research, 2012)
Three highly effective alien genes for leaf rust resistance, Lr 24, Lr 28 and Lr 9 were selected for pyramiding in the background of a susceptible but well adapted bread wheat variety HD 2329. Screening against most virulent pathotypes of leaf rust 77-5 (121R63-1) indicated that all the three genes confer a high degree of seedling and adult plant resistance. The use of molecular markers, namely, SCS1302607, SCS421570 and SCSS5550 validated the presence of the linked genes resistance genes, Lr 24, Lr 28 and Lr 9 in the three rust resistant near isogenic lines (NILs) of HD 2329. The application of molecular markers facilitated identification of individual plants in threeway cross (HD 2329+Lr 24 x HD 2329+Lr 28) x HD 2329 + Lr 9, F1 and F2 generations possessing the targeted genes. Finally, one bulked progeny in F8 generation was identified carrying the desired resistance genes, Lr 24, Lr 28 and Lr 9 in homozygous condition in the background of HD 2329. The availability of a combination of the three major rust resistance genes in desirable background would facilitate the strategic deployment of wheat varieties to achieve durable resistance.